2018
DOI: 10.1002/1873-3468.13004
|View full text |Cite
|
Sign up to set email alerts
|

The role of OleA His285 in orchestration of long‐chain acyl‐coenzyme A substrates

Abstract: Renewable production of hydrocarbons is being pursued as a petroleum-independent source of commodity chemicals and replacement for biofuels. The bacterial biosynthesis of long-chain olefins represents one such platform. The process is initiated by OleA catalyzing the condensation of two fatty acyl-coenzyme A substrates to form a β-keto acid. Here, the mechanistic role of the conserved His285 is investigated through mutagenesis, activity assays, and X-ray crystallography. Our data demonstrate that His285 is req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The roles of active site residues H285, E117, and C143 of OleA have been studied using site-directed mutagenesis and X-ray crystal structures. All of these residues are important for the first step of olefin biosynthesis. OleD is an NAD­(P)­H-dependent reductase and a member of the short-chain dehydrogenase superfamily which catalyzes reduction of β-keto acid to generate β-hydroxy acid . OleC is a β-lactone synthetase found in X. campestris , S. maltophilia, Micrococcus luteus , Lysobacter dokdonensis , and Arenimonas malthae which catalyzes β-lactone synthesis from β-hydroxy acid .…”
Section: Production Of Triglyceride- Fatty Acid- and Glycerol-derived...mentioning
confidence: 99%
“…The roles of active site residues H285, E117, and C143 of OleA have been studied using site-directed mutagenesis and X-ray crystal structures. All of these residues are important for the first step of olefin biosynthesis. OleD is an NAD­(P)­H-dependent reductase and a member of the short-chain dehydrogenase superfamily which catalyzes reduction of β-keto acid to generate β-hydroxy acid . OleC is a β-lactone synthetase found in X. campestris , S. maltophilia, Micrococcus luteus , Lysobacter dokdonensis , and Arenimonas malthae which catalyzes β-lactone synthesis from β-hydroxy acid .…”
Section: Production Of Triglyceride- Fatty Acid- and Glycerol-derived...mentioning
confidence: 99%
“…Another homologous protein pair, LstAB, is a heterodimer made by Streptomyces toxytricini that produces lipstatin, which is hydrogenated to make the antiobesity drug tetrahydrolipstatin, known commercially as Orlistat or Xenical [16] , [24] . The best studied enzyme catalyzing these condensation reactions with long chain substrates is the OleA from the plant pathogen Xanthomonas campestris [17] , [25] , [26] , [27] , [28] .
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…X-ray structures of the X. campestris OleA enzyme have been solved to 1.8 Å resolution, helping to reveal features of the Claisen condensation reaction [25] , [26] , [27] , [28] . Initial studies with native enzyme and inhibitors revealed the reactivity of Cys143 and the occupation of a hydrophobic tunnel denoted as Channel A ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As such, there is significant interest in identifying and reengineering these enzymes for biotechnological purposes (14). Our understanding thus far is derived almost exclusively from mechanistic and X-ray crystallographic studies with OleA from X. campestris (15)(16)(17)(18) and a study on hydrocarbon biosynthesis in Micrococcus luteus (19). X. campestris OleA catalyzes the condensation of acyl-CoA substrates with C 10 -C 16 acyl chains and produces long-chain hydrocarbons via deoxygenation reactions catalyzed by OleC and OleB proteins.…”
mentioning
confidence: 99%